Impact assessment study of BRAC's Rural Development Programme: final report (unedited draft for comments) - Mustafa, Shams; Ara, Ishrat; Banu, Dilruba; Hossain, Altaf; Kabir, Ajmal; Mohsin, Mohammad; Yusuf, Abu (© BRAC, 2016)
1. Introduction 2. The rural development programme 3. Methodology of the impact assessment study 4. The contextual factors 5. Measuring RDP inputs 6. Material well-being of RDP households 7. Vulnerability and coping capacity 8. Changes in women's lives 9. Village organizations and institutional development 10. Non-formal primary education programme